Incorporation of Steel Fibers to Enhance Performance of Sustainable Concrete Made with Waste Brick Aggregates: Experimental and Regression-Based Approaches - Yooprasertchai, Ekkachai; Bahrami, Alireza; Saingam, Panumas; Hussain, Qudeer; Ejaz, Ali; Joyklad, Panuwat (My University, 2023)
Each year, an enormous amount of construction waste is produced worldwide. The reuse of construction waste in construction works is a sustainable solution. The present research work utilized recycled brick aggregates in the production of concrete. The resulting concrete exhibited substandard splitting tensile, flexural, and compressive properties. Steel fibers were used to improve these substandard properties of recycled brick aggregate concrete. The volume fractions of 1%, 2%, and 3% for steel fibers were mixed in concrete, whereas recycled brick aggregates were obtained from solid fired-clay bricks, hollow fired-clay bricks, and cement–clay interlocking bricks. The compressive strength was enhanced by up to 35.53% and 66.67% for natural and recycled brick aggregate concrete, respectively. Strengthened flexural specimens demonstrated up to 8765.69% increase in the energy dissipation. Specimens strengthened with steel fibers showed substantially improved splitting tensile, flexural, and compressive responses. Separate equations were proposed to predict the peak compressive strength, strain at peak compressive strength, elastic modulus, and post-peak modulus of recycled brick aggregate concrete. The proposed regression equations were utilized in combination with an existing compressive stress–strain model. A close agreement was observed between experimental and predicted compressive stress–strain curves of recycled brick aggregate concrete.
Keywords: analytical modeling; compressive strength; energy dissipation; flexural strength; recycled brick aggregate; regression; splitting tensile strength; steel fiber